The Composition and the Content of ∆-5 Sterols, Fatty Acids, and the Activity of Acyl-Lipid Desaturases in the Shoots of Ephedra monosperma, Introduced in the Botanical Garden of the Cryolithozone of Yakutia - Vasiliy V. Nokhsorov; Luybov V. Dudareva; Natalia V. Semenova; Valentina E. Sofronova (Horticulturae, 2023)
Evergreen plants in permafrost ecosystems survive unfavorable autumn cooling and extremely low winter temperatures by maintaining optimal physiological activity of tissue cell membranes. To some extent, these features are due to the properties of shoot lipids performing a number of functions during adaptation. Sterols (STs) play a key role in regulating the fluidity and permeability of plant membranes (phytosterols) with a wide structural diversity. The composition of neutral lipids, STs, and fatty acids (FAs) in shoots of the evergreen shrub Ephedra monosperma growing in the Botanical Garden cryolithozone was first studied with HPTLC-UV/Vis/FLD and GC-MS. Twenty FAs were found, from C14:0 to C23:0; they included mono-, di-, tri-, and tetraene FAs. The high content of β-sitosterol among other ∆-5 sterols and an increased amount of C18:2(∆9,12) linoleic acid in lipids composition during the autumn–winter period was found to play an important role in the adaptation of ephedra shoots to the autumn–winter period, providing the cell membrane with greater plasticity, fluidity, and flexibility. The important role of diene linoleic fatty acid C18:2(∆9,12) in ephedra shoot lipids in the processes of low-temperature adaptation was shown.